THE PATHOGENESIS OF IRON DEFICIENCY ANEMIA IN OBESITY - V.M. Nedoborenko; I.P. Kaidashev (Проблеми екології та медицини)
Iron deficiency anemia and obesity have become a global problem affecting not only high income countries but also developing countries. Experimental and clinical studies indicate that there is a relationship between iron metabolism and weight status. Obesity is associated with low-grade systemic inflammation and elevated hepcidin concentrations. Hepcidin is the key regulator of systemic iron homeostasis. This review summarizes the current understanding of the dysregulation of iron homeostasis in obesity and leads assumptions about treatment.